Switchable magnetic, dielectric, conductivity, and phase transition properties of charge-transfer crystals - Yu, S. S.; Zhao, H. R.; Xu, W.; Zhang, H.; Duan, H. B. (Frontiers in Electronic Materials, 2022)
The properties can be switched between different states and can be used in sensors, displays, and memory devices. In this study, two multi-functional switchable materials [C5-Pmim][Ni(mnt)2] (1) and [C6-Hmim][Ni(mnt)2] (2) (where mnt2- = maleonitriledithiolate, C5-Pmim = 1-pentyl-3-methylimidazolium, and C6-Hmim = 1-hexyl-3-methylimidazolium) have been designed and synthesized, which has segregated cation and anion stacks in the crystal structure. 1 shows two-step switchable dielectric transition with a thermal hysteresis loop accompanying structure phase transition. Dielectric transition of 1 can be attributed to the reorientation of the polar cations and crystal to mesophase transition. Switchable conductivity properties of 1 and 2 were realized by the crystal to mesophase structure transition. The conductivity of the mesophase for 1 and 2 is higher than the corresponding crystal phase. Furthermore, magnetic phase transition with the non-common hysteresis loop for 2 is observed being triggered by the structure and dielectric transition. To the best of our knowledge, this study might be the rare multi-functional switchable examples with dielectric, conductivity, and magnetic transition.